JIHAD PEREMPUAN DAN TERORISME - Udji Asiyah; Ratna Azis Prasetyo; Sudjak Sudjak (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
The wrong meaning in understanding religious commands like jihad, has an impact on the orientation of one’s actions that can lead to evil both to himself and to others. Similarly, the rampant suicide bombing cases involving women covered in various media. This article seeks to examine the extent to which the involvement of women in suicide cases is determined by how he interpreted the jihad and the orientation of his actions and the patriarchal dominance that surrounds him. The cases of female suicide bombs related to terrorism are reported from various media can provide information about the relationship between religious concepts, action orientation and patriarchal domination. This paper reveals that the involvement of women in the case of terrorism is not off the related theme of giving meaning to the concept of religion and the orientation of action and patriarchal domination.